21.1k views
3 votes
Can someone solve this? also, show work please. We need to find out what x is.

-6x + 13 = -5(7 +6x)​

1 Answer

2 votes

Answer:
\huge{ \boxed{ \bold{ \tt{ x = - 2}}}}

Explanation:


\sf{ - 6x + 13 = - 5(7 + 6x) }

Distribute -5 through the parentheses


\longrightarrow{ \sf{ - 6x + 13 =  - 5 * 7  + ( - 5 )* 6x}}


\longrightarrow{ \sf{ - 6x  + 13 =  - 35 + ( - 30x)}}


\text{Remember} : \sf{( + ) * ( - ) = ( - )}


\longrightarrow{ \sf{ - 6x + 13 =  - 35 - 30x}}

Move 30x to left hand side and change it's sign


\longrightarrow{ \sf{ - 6x + 30x + 13 = - 35}}

Move 13 to R.H.S ( Right Hand Side ) and change it's sign
\longrightarrow{ \sf{ - 6x + 30x= - 35 - 13}}

Combine like terms


\longrightarrow{ \sf{24x = - 35 - 13}}

The negative integers are always added but posses the negative ( - ) sign.
\longrightarrow{ \sf{24x = - 48 }}

Divide both sides by 24


\longrightarrow{ \sf{ (24x)/(24) = ( - 48)/(24)}}

Dividing a negative integer by a positive integers gives a negative integer.


\longrightarrow{\sf{x = -2 }}

-----------------------------------------------------

Verification:

L.H.S = -6x + 13

Plug the value of x and simplify


\longrightarrow{ \sf{ - 6 * ( - 2) + 13}}

Multiplying negative integers by a negative integer gives a positive integer.


\longrightarrow{ \sf{ 12 + 13}}

Add the numbers : 12 and 13


\longrightarrow{ \sf{25}}

R.H.S = -5 ( 7 + 6x )

plug the value of x and simplify


\longrightarrow{ \sf{ - 5(7 + 6 * ( - 2)}})

Multiplying a positive integer by any negative integer gives a negative integer.


\longrightarrow{ \sf - 5(7 + ( - 12)}


\longrightarrow{\sf{-5(7 - 12)}}

Subtract 12 from 7


\longrightarrow{ \sf{ - 5 * ( - 5)}}


\longrightarrow{\sf{25}}

L.H.S = R.H.S

The value of x is -2 .

Hope I helped!

Best regards!

~TheAnimeGirl

User Niriel
by
5.3k points